Pendidikan Akal Perspektif Hadis: Telaah Metode Praktik Langsung, Pengulangan, Penjelasan, dan Perumpamaan - Saidah Khadijah Shabira; Navira Navira; Lisa Amelia Siregar (Jurnal Pendidikan Agama Islam, 2026)
Intellect is a vital gift that serves as the foundation for understanding and practicing Islamic teachings. In the Hadith, intellectual education receives significant attention because it determines how to think, religious awareness, and correct behavior. This article aims to examine the concept of intellectual education by examining various hadiths of the Prophet and previous research. The method used is a literature study with a descriptive-analytical approach based on data collection from hadith books, Islamic education books, and scientific journals. The results of the study show that there are four methods in intellectual education: (1) direct practice, namely learning that shows students how the process of something takes place. (2) repetition, strengthening memory so that it is easy to understand and firmly embedded in the minds and hearts of students. (3) explanation, providing a clear and logical understanding so that the human mind can digest the teachings well. (4) parables, training the human mind to make analogies so that more precise conclusions are obtained. These four methods have proven effective in developing critical and in-depth thinking patterns in students. This study recommends the use of direct practice, repetition, explanation, and metaphor in learning so that Islamic education can produce not only an intellectually intelligent generation but also one with moral and spiritual intelligence